Changes in body composition (muscle mass and adipose tissue) among adolescents aged 11–15 from Kraków during the COVID-19 pandemic - Paulina Artymiak; Magdalena Żegleń; Łukasz Kryst (Anthropological Review)
Study aim: To assess changes in body composition, specifically focusing on muscle mass and adipose tissue, among adolescents aged 11–15 in Kraków during the COVID-19 pandemic.